Combustion optimization control system based on acoustically-measured hearth temperature field, and control method thereof - LIU FUGUO; DONG XINGUANG; YANG XINGSEN; HAO WEIDONG; HU ZHIHONG (2013)
The invention discloses a combustion optimization control system based on acoustically-measured hearth temperature field, and a control method thereof. The system comprises a data acquisition device, a data processing device, an operating mode selector module, and an execution instruction output module. A coal quality processing module, a soot blowing mode processing module, an auxiliary air distribution mode processing module, a hearth temperature field data processing module, a hearth temperature field homogenizing module, a boiler auxiliary operating mode processing module, and a boiler coal mill commissioning mode processing module are packaged in the data processing device. The execution instruction output module comprises an oxygen adjustment module and a hearth temperature adjustment module. The combustion optimization control system based on acoustically-measured hearth temperature field and the control method thereof have the advantages that interior combustion conditions can be quickly and directly